ANALISIS USABILITY TESTING APLIKASI TOKOCRYPTO - Fadillah, Muhammad; Mulyani, Astriana (Journal of Information System, Applied, Management, Accounting and Research, 2024)
This study aims to analyze the Usability testing of the Tokocrypto application to improve the quality of the user experience. The problems identified in this application include the unavailability of charts in the wallet, the lack of clear indicators to distinguish between rising and falling assets, and the availability of many unclear coins that create confusion for users. The methods used in this study included test planning, participant recruitment, data collection through observation, interviews, and questionnaires, and data analysis to identify problem patterns and areas of improvement. The results show that improvements to these aspects can significantly enhance user experience, make it easier for users to monitor asset movements, and manage portfolios more efficiently.